A new optimization design for grounding grid. (June 2019) - Hu, Haize; Luo, Richeng; Fang, Mengge; Zeng, Shuiling; Hu, Feiyu
Highlights: The dual port model is used for ground conductor calculations and the EMF ground grid standard model is used for comparative analysis. The relationship between the various induced voltages of the grounding grid and the lightning current injection point is studied by using the dual port model. A comparative study of auxiliary annular grounding grid and square grounding grid is discussed. The characteristics of the first grounding discharge with the auxiliary grounding grid instead of the main grounding grid is discussed. Abstract: In this paper, a new approach for designing groudging grid is proposed. The design is based on constracting an auxiliary annular grounding grid and transforming the lingtning rod's grounding poing from main grounding grid to auxiliary grounding grid. Modal analysis and softwave simulataes is employed to obtain the transformed lightning current (and the voltage) and the reduced ressitance. The dual port model is used to calculate the impedance value of the grounding grid. The calculation results of the model are compared with the standard grounding body model EMF. At the same time, the relationship between the induced voltage of each point of the grounding grid and the distance of the lightning current injection point is studied by using the dual port model. The reduced resistance is simulated by building annular grounging grid model and square grounging grid model and making a comparison in performance betwen them. Farther, when there is a lingtning event, instead of providing a low impedance path by the main grounding grid, the design provide anther path by the auxilary grounding grid, which can transfer the lightning current into the auxilary grounding grid. All the model analysis and simulation results are presented and discussed in the paper.